FORESIGHT IN FUTURE STUDIES OF RUSSIAN EDUCATION - Irina R. Nazarova (Высшее образование в России)
The article describes the possibilities of foresight in determining the long-term prospects of development of society and its institutions, including the institution of education. Stresses the necessity of taking into account national, political, socio+economic aspects when carrying out foresight. The article substantiates the importance of the effective work of the Institute of social partnership, and responsibility for the decisions in the field of educationalreform.